Diffusion under micro-gravity-Mass transfer from rising bubble in a stagnant fluid column - Bari, Md Ashfaqul; Akbulut, Cemil; Münsch, Manuel; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2018)
Numerical simulation of two‐phase flows using Volume of Fluid (VOF) method is known be to susceptible to parasitic currents, which arises due to erroneous interface curvature calculation to model the surface tension force. The interface curvature calculation scheme in OpenFoam has been modified according to the Sharp Surface Force (SSF) which reduced parasitic currents magnitude significantly. Alongside SSF method the Continuous Species Transfer (CST) equation is implemented in OpenFOAM 4.1 to simulate mass transfer from an Oxygen bubble to the surrounding stagnant water‐glycerol solution under micro‐gravity environmen
Keywords: Diffusion; Micro-gravity; OpenFOAM